2020
DOI: 10.1177/0003319720917239
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in Ruptured Aortic Aneurysm in the United States: A Retrospective Analysis of Nationwide Inpatient Sample Database

Abstract: We assessed the trend of palliative care (PC) referrals and its effect on hospitalization cost and length of stay (LOS) in ruptured aortic aneurysm (rAA). The Nationwide Inpatient Sample from 2005 to 2014 was used to identify admissions with age ≥50 and rAA. A total of 54 134 rAA admissions were identified and 5019 (9.3%) had PC referrals. During the study period, PC referral rate increased from 0.97% to 15.3% ( P trend < .0001). Length of stay (1.7 vs 2.8 days, adjusted mean ratio [aMR] = 0.62, 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The present meta-analysis provided an updated overview on the association between egg consumption and CVD risk and mortality: compared to previous meta-analyses, we included the highest number of cohorts reviewed to date, several dose–response analyses for the investigated outcomes, a detailed investigation for potential confounding factors by studying subgroups and stratifying the analyses, and we attempted an evaluation of the overall evidence. Previous meta-analyses reported rather mixed results, with no association with stroke risk [ 55 ], decreased risk of stroke and no association with CHD [ 56 , 57 ], decreased risk of CHD [ 58 ], no association with CVD risk [ 59 ], increased risk of heart failure [ 60 , 61 ],compared to these studies, our analysis is more complete and provides a general more in depth analysis of level of evidence. We generally found no strong association with either increased or decreased risk of cardiovascular outcomes following the habitual consumption of eggs (i.e., one egg per day compared to no intake), with exception of risk of heart failure, which resulted higher especially in men from US cohorts.…”
Section: Discussionmentioning
confidence: 86%
“…The present meta-analysis provided an updated overview on the association between egg consumption and CVD risk and mortality: compared to previous meta-analyses, we included the highest number of cohorts reviewed to date, several dose–response analyses for the investigated outcomes, a detailed investigation for potential confounding factors by studying subgroups and stratifying the analyses, and we attempted an evaluation of the overall evidence. Previous meta-analyses reported rather mixed results, with no association with stroke risk [ 55 ], decreased risk of stroke and no association with CHD [ 56 , 57 ], decreased risk of CHD [ 58 ], no association with CVD risk [ 59 ], increased risk of heart failure [ 60 , 61 ],compared to these studies, our analysis is more complete and provides a general more in depth analysis of level of evidence. We generally found no strong association with either increased or decreased risk of cardiovascular outcomes following the habitual consumption of eggs (i.e., one egg per day compared to no intake), with exception of risk of heart failure, which resulted higher especially in men from US cohorts.…”
Section: Discussionmentioning
confidence: 86%
“…The lower palliative care consultation utilization in younger patients, non-White race, lower income patient and smaller/non-teaching hospitals has been reported in previous studies with other medical issues. 9,21 Though our study does not identify subsets of patients that would benefit most from palliative care consultation, there is likely room to improve patient-selection for appropriate palliative care consultation in patients with Staphylococcus aureus bacteremia. In addition, a recent study revealed that Staphylococcus aureus bacteremia leads to a significant impact on the quality of life among survivors.…”
Section: Discussionmentioning
confidence: 97%
“…A similar study demonstrated that palliative care consultation was placed in 11 and 15% of patients with ST-segment elevation myocardial infarction and abdominal aortic rupture, respectively. 9,20 The lower rate of palliative care consultation in Staphylococcus aureus bacteremia may be explained by infection being viewed as more treatable (with antibiotics) than other conditions considered to be irreversible. However, palliative care consultation was used in only one third of Staphylococcus aureus bacteremia patients who died during their hospitalization (34% of 12971; 4314 patients).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations